Honduras : Third Reviews Under the Stand-By Arrangement and Arrangement Under the Standby Credit Facility, Requests for Extension and Rephasing of the Arrangements, Waiver of Nonobservance of Performance Criterion, and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Honduras. (IMF Staff Country Reports; Country Report ;, 2020)
The near-term outlook has worsened, while a recovery is expected for next year. Amid a weak health system and a surge in infections over the summer, the gradual reopening of the economy has faced setbacks and the pandemic is having a stronger and more protracted social and economic impact than expected. While the policy response to the Covid-19 shock was appropriately designed, there have been implementation challenges and delays. The authorities' monitoring system of pandemic-related spending and civil society oversight helped identify missteps to implement corrective actions, for which they are receiving technical assistance from FAD and the Inter-American Development Bank (IDB). More recently, Honduras is also facing the challenge to respond to two tropical storms, which the authorities intend to manage within the contour of the current economic program.